Characteristics of the Influence of Parental Relationships on the Development of Empathy in Children - Eshmamatov Bahodir Xolmurza o'g'li (Scientific Trends, 2024)
This study examines the role of parental relationships in shaping the development of empathy in children, emphasizing the specific characteristics of these influences. Empathy, a crucial social-emotional skill, is significantly affected by the emotional and behavioral patterns modeled by parents. The article explores theoretical frameworks, empirical evidence, and cultural nuances, including insights from Uzbek culture, to analyze how parental interactions contribute to the formation of empathetic abilities in children.
Keywords: Parental relationships, empathy development, child psychology, family dynamics, Uzbek culture, socio-emotional skills.